Optimalisasi Peran Ibu dalam Pijat Bayi Melalui Kelas Ibu Bayi: Optimizing the Mother’s Role in Baby Massage Through Mother-Baby Classes - Putri, Noviyati Rahardjo; Dharmawan, Caroline; Larasati, Disa; Septiana, Yesika Cahya; Amalia, Riza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Baby massage can improve sleep quality and stimulate growth and development. The application of baby massage by mothers is still rare and not common because the training provided has not yet become a culture in society, even though baby massage by mothers can reduce symptoms of anxiety, and depression, increase bonding and attachment, and optimize the breastfeeding process. One effort to improve baby massage behavior is with parent classes for baby massage. This activity aims to provide mothers with experience in practicing baby massage regularly over 5 meetings guided by a certified instructor. The result of community service is that mothers feel confident in doing baby massages independently. The parent class for baby massage activity is expected to become a routine program for every baby mother, such as classes for pregnant women to achieve optimal maternal and child health.